Profile of HIV post-exposure prophylaxis users at the Urgent Care Center of Icoaraci, Belém, Pará (Research, Society and Development, 2025)
Objective: To investigate the profile of PEP/HIV users at the UPA in Icoaraci, Belém, Pará. Methodology: Cross-sectional, retrospective, exploratory research, with a time frame between 2022 and 2024, using medical records for sociodemographic characterization, among others. Data were analyzed using descriptive and inferential statistics, including measures of central tendency and variability, adopting a p-value